Asupan Zat Gizi Antenatal dan Kejadian Stunting pada Anak: Systematic Review - Umrah Sri Rahayuh Afandy; Lydia Fanny; Mustamin Mustamin (Poltekkes Kemenkes Semarang, 2024)
Background: The Indonesian Ministry of Health's Nutritional Status Study reported that the prevalence of stunting in Indonesia in 2022 was 21.6%. Although there has been a decrease, this figure still does not meet the WHO standard of less than 20%. Stunting is a condition where a child is shorter than their peers, experiencing growth failure due to poor nutrition, recurrent infections, and inadequate psychosocial stimulation from early life. Pregnancy is a crucial period and represents a golden opportunity for a child to grow and develop normally. Objective: The purpose of this study is to analyze whether maternal intake during pregnancy is related to the occurrence of stunting.Research Methods: This study is a literature review that uses primary data research articles on maternal nutritional intake during pregnancy related to the incidence of stunting. The data sources used are research journal publications conducted in Indonesia. Article searches were conducted using the Google Scholar database search engine. The inclusion criteria for journals in this study are research journals on antenatal nutrient intake related to the incidence of stunting, published between 2014 and 2024, and freely accessible.Results: The literature review results show that nutrient intake during the antenatal period affects the incidence of stunting in children. Mothers who consume insufficient iodine, carbohydrates, proteins, fats, and folic acid during pregnancy are more likely to give birth to stunted babies.Conclusion: There is a significant relationship between nutrient intake during pregnancy and the incidence of stunting in children. Mothers with deficiencies in carbohydrates, proteins, fats, iodine, and/or folic acid are at a higher risk of giving birth to stunted children.